Juridical Study of The Multi-Interpretation Clause of Tourism Agreements in The Digital Era - Santhi, Ni Nyoman Putri Purnama; Kosasih, Johannes Ibrahim (West Science Interdisciplinary Studies, 2025)
Tourism business contracts in the digital era often trigger disputes. This is because the parties involved in the business contract are subject to different legal systems. Apart from that, contracts signed by the parties still contain clauses that contain multiple interpretations. Contracts that should become law for the parties actually become a source of dispute. This research aims to conduct a juridical study of multi-interpretation clauses in tourism agreements in the digital era. This research uses a normative method by examining statutory regulations, books, journals, and articles relating to tourism business contracts and multi-interpretation clauses. The research results show that the existence of multiple interpretation clauses in tourism business contracts can trigger disputes that hinder the development of the tourism industry. Therefore, efforts are needed to draft clear and firm clauses and pay attention to legal harmonization so that tourism business contracts can provide legal certainty and protect the parties involved.